The scope of responsibility of employers towards workers’ families in the Second Republic of Poland - Grata, Paweł (Annales. Etyka w Życiu Gospodarczym, 2019)
The aim of this article is the presentation of the scope of responsibility of employers towards workers’ families in Poland in the interwar period. The article also shows how those duties were fulfilled. This issue appeared in Europe with the development of social insurance programmes and labour laws. The Second Republic of Poland built its own legal system for employees’ families. It included health insurance and benefits, families’ pensions and funeral allowances. Certain obligations were also imposed on employers in the context of labour law. The most important was the obligation to open nursery schools for the children of women who worked in factories.